2012
DOI: 10.5194/acp-12-2313-2012
|View full text |Cite
|
Sign up to set email alerts
|

Xenon-133 and caesium-137 releases into the atmosphere from the Fukushima Dai-ichi nuclear power plant: determination of the source term, atmospheric dispersion, and deposition

Abstract: Abstract. On 11 March 2011, an earthquake occurred about 130 km off the Pacific coast of Japan's main island Honshu, followed by a large tsunami. The resulting loss of electric power at the Fukushima Dai-ichi nuclear power plant developed into a disaster causing massive release of radioactivity into the atmosphere. In this study, we determine the emissions into the atmosphere of two isotopes, the noble gas xenon-133 (133Xe) and the aerosol-bound caesium-137 (137Cs), which have very different release characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
387
6
24

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(432 citation statements)
references
References 42 publications
15
387
6
24
Order By: Relevance
“…'The FDNPP accident that occurred on 11 March 2011 was a highly significant event for marine radioecology, since about 80% of the radioactive fallout occurred over the Pacific Ocean (IAEA, 2015;Sanial et al, 2017;Stohl et al, 2011;UNSCEAR, 2014), especially in coastal waters near the FDNPP. Direct discharges of radionuclides to the ocean continued during the first months after the accident, as a consequence of emergency cooling efforts at the FDNPP (Buesseler et al, 2011), whereas atmospheric releases ceased in a few days.…”
Section: State Of Knowledge On the Impact Of The Fdnpp Accident On Thmentioning
confidence: 99%
“…'The FDNPP accident that occurred on 11 March 2011 was a highly significant event for marine radioecology, since about 80% of the radioactive fallout occurred over the Pacific Ocean (IAEA, 2015;Sanial et al, 2017;Stohl et al, 2011;UNSCEAR, 2014), especially in coastal waters near the FDNPP. Direct discharges of radionuclides to the ocean continued during the first months after the accident, as a consequence of emergency cooling efforts at the FDNPP (Buesseler et al, 2011), whereas atmospheric releases ceased in a few days.…”
Section: State Of Knowledge On the Impact Of The Fdnpp Accident On Thmentioning
confidence: 99%
“…Various researchers have estimated its source term during FDNPP accident using inverse estimation methods (Stohl et al, 2012;Terada et al, 2012;Oza et al, 2013;Katata et al, (Katata et al, 2015). Cs emission rate (Katata et al, 2015) as shown in Fig.…”
Section: Caesium-137mentioning
confidence: 99%
“…The total amount of 137 Cs discharged into the atmosphere between 12 March and 6 April 2011 was estimated as approximately 1.3 × 10 16 Bq (Chino et al 2011 ). Before 20 April 2011, 18 % of the total fallout settled on Japanese land (Stohl et al 2012 ). Radiocesium monitoring of freshwater organisms (Fisheries Agency 2012 ) showed that trophic level is an important ecological factor affecting bioaccumulation of 137 Cs in fi sh (Mizuno and Kubo 2013 ).…”
Section: Introductionmentioning
confidence: 99%